2020
DOI: 10.2147/vmrr.s266350
|View full text |Cite
|
Sign up to set email alerts
|

<p>Epidemiological Investigation of Cattle Abortion and Its Association with Brucellosis in Jimma Zone, Ethiopia</p>

Abstract: Background: The epidemiology of cattle abortion and its association with brucellosis is not well understood in Ethiopia. Therefore, the aim of this study was to determine the magnitude, associated risk factors of abortion, and its association with brucellosis in cattle of Jimma zone, Ethiopia. Methods: A cross-sectional study was carried out from October 2018 to October 2019 in Jimma zone. A total of 484 pregnant cattle were randomly selected from two districts based on the composition of the cattle population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
7
10
1
Order By: Relevance
“…The highest incidence of pregnancy loss in buffaloes occurred within the first trimester, with 3.3% of all cases in this study. This agrees with the results of Deresa et al [33] in cows and Vecchio et al [34] in buffaloes, who found that there was a significantly (p < 0.01) higher incidence of abortion during 28-60 days of gestation and lower after 71 days of gestation. Those authors suggest that the higher incidence of abortion could be due to the lower levels of serum progesterone that normally found in the transitional period (from 3 weeks to 3 weeks after calving) in buffalo cows.…”
Section: Discussionsupporting
confidence: 93%
“…The highest incidence of pregnancy loss in buffaloes occurred within the first trimester, with 3.3% of all cases in this study. This agrees with the results of Deresa et al [33] in cows and Vecchio et al [34] in buffaloes, who found that there was a significantly (p < 0.01) higher incidence of abortion during 28-60 days of gestation and lower after 71 days of gestation. Those authors suggest that the higher incidence of abortion could be due to the lower levels of serum progesterone that normally found in the transitional period (from 3 weeks to 3 weeks after calving) in buffalo cows.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the safety of A19ΔvirB12 was evaluated in large-scale pregnant cattle. Previous epidemiological studies have shown that the occurrence of cattle abortion is caused by multiple factors ( 25 ). In the same pasture, the occurrence of cattle abortion is mainly related to seasonal variation.…”
Section: Resultsmentioning
confidence: 99%
“…Abortion is the most frequent cattle reproduction problem in Ethiopia. For instance, it has been reported as widespread in the Jimma zone, compromising cattle health and production ( Regassa and Ashebir, 2016 ; Deresa et al., 2020 ). However, the investigation of the causes of abortion has always been challenging in developing countries like Ethiopia mainly due to resource limitations for laboratory diagnostic.…”
Section: Discussionmentioning
confidence: 99%